Development of PLGA micro- and nanorods with high capacity of surface ligand conjugation for enhanced targeted delivery - Jiafu Cao; Jin-Seok Choi; Murtada A. Oshi; Juho Lee; Nurhasni Hasan; Jihyun Kim; Jin-Wook Yoo (Elsevier, 2019)
Particle shape has been recognized as one of the key properties of nanoparticles in biomedical applications including targeted drug delivery. Targeting ability of shape-engineered particles depends largely on targeting ligands conjugated on the particle surface. However, poor capacity for surface ligand conjugation remains a problem in anisotropic nanoparticles made with biodegradable polymers such as PLGA. In this study, we prepared anisotropic PLGA nanoparticles with abundant conjugatable surface functional groups by a film stretching-based fabrication method with poly (ethylene-alt-maleic acid) (PEMA). Scanning electron microscopy images showed that microrods and nanorods were successfully fabricated by the PEMA-based film stretching method. The presence of surface carboxylic acid groups was confirmed by confocal microscopy and zeta potential measurements. Using the improved film-stretching method, the amount of protein conjugated to the surface of nanorods was increased three-fold. Transferrin-conjugated, nanorods fabricated by the improved method exhibited higher binding and internalization than unmodified counterparts. Therefore, the PEMA-based film-stretching system presented in this study would be a promising fabrication method for non-spherical biodegradable polymeric micro- and nanoparticles with high capacity of surface modifications for enhanced targeted delivery. Keywords: Particle shape, PLGA nanoparticles, Film-stretching method, Surface modification, Targeted drug delivery